Research of Gear Form Grinding Burn based on Grinding Power Measurement and Barkhausen Nondestructive Test - Jun Yi; Tan Jin; Mingdong Zhang (Jixie chuandong)
The strength，service life and reliability of gears are seriously affected by grinding burn. The gear form grinding experiments with different grinding parameters are carried out to measure the grinding power during the grinding process. After grinding，the tooth profile is tested by Barkhausen nondestructive test and microhardness test. The effects of different grinding parameters on the grinding power and the RMS values of the Barkhausen signal of the tooth profile are analyzed. A theoretical basis for the study of burn in gear form grinding is provided by this work.